Detection of avian leukosis virus using polymerase chain reaction and enzyme linked immunosorbent assay - Thapa Chhetri, Bala Ram; Abd Rasid, Omar; Md Mahfuzul Hoque; Arshad, Siti Suri; Bejo, Mohd Hair (Veterinary Association Malaysia, 2004)
The applications of polymerase chain reaction (PCR) and enzyme linked immunosorbent assay (ELISA) in detecting avian leukosis virus (ALV) subgroups A and J were studied in a flock of breeder chickens. Out of 74 chickens tested 9, 36, 13 and 16 were found positive for both p27/gp85, negative for both, positive for p27 and positive for gp85, respectively. All the chickens that were found positive for p27 antigen were also positive for subgroup A proviral DNA. Although 25 chickens were positive for subgroup J gp85 antibody, none of the chickens were found positive for subgroup J proviral DNA. Hence, detection of p27 antigen from cloacal swab was found to correlate more with detection of proviral DNA. However, none of the chickens were found positive for viral RNA and did not shed infectious viruses. In conclusion, accurate diagnosis of ALV infection requires more than one laboratory test for confirmation.